Study of Ag2O/TiO2 nanowires synthesis and characterization for heterogeneous reduction reaction catalysis of 4-nitrophenol - Yunarti, R.T.; Isa, I.D.; Dimonti, L.C.C.; Dwiatmoko, A.A.; Ridwan, M.; Ha, J.-M. (Elsevier B.V., 2021)
Ag2O/TiO2 nanowires as catalyst for reduction reaction of 4-nitrophenol has been synthesized in this study with molten-salt route and followed by the impregnation method. Analysis by characterization results show that the addition of Ag2O does not change TiO2 crystal structure and morphology, and it was found that the impregnated Ag2O has metal-support interactions with TiO2 nanowires. Size distribution of TiO2 nanowires structure along with the Ag2O is known to be within the range of nanomaterial. TiO2 nanowires has an average width of 339.706 nm, and the impregnated Ag2O has an average diameter size of 19.873 nm respectively. The catalytic test performance shows that Ag2O/TiO2 nanowires has excellent result compared to the control sample morphology of Ag2O/TiO2 anatase. It is closely correlated with the electron transfer capability of TiO2 nanowires structure and this shows that Ag2O/TiO2 nanowires is suitable for catalysis of 4-nitrophenol reduction reaction. ？ 2021 Elsevier B.V.